1986
DOI: 10.1039/c39860001545
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically selective pig liver esterase-catalysed hydrolyses of racemic allenic esters

Abstract: Pig liver esterase-catalysed hydrolyses of variously substituted racemic allenic esters proceed with predictable enantiomeric selectivity, with the highest (93%) enantiomeric excess values being observed for the most highly substituted substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However, only two substrates (R 1 = Ph, R 2 = R 3 = Me or Et) afforded the corresponding 2,3allenoic acids with >90% ee (Scheme 31). 37 For 2-substituted axially chiral 2,3-allenols, this group found that PPL is an optimal enzyme for the resolution of this type of substrates; for example, trisubstituted 2,3-allenol (S)-97 was obtained with 99% ee, albeit in low yield (eqn (1), Scheme 32). 38 Bäckvall et al studied the kinetic resolution of this type of allenols using vinyl butyrate as the acyl donor and found that 4-aryl substituted allenols were resolved more efficiently than 4-alkyl substituted ones, affording the corresponding allenyl esters (R)-100 with excellent enantioselectivity.…”
Section: From Racemic Allenesmentioning
confidence: 99%
“…However, only two substrates (R 1 = Ph, R 2 = R 3 = Me or Et) afforded the corresponding 2,3allenoic acids with >90% ee (Scheme 31). 37 For 2-substituted axially chiral 2,3-allenols, this group found that PPL is an optimal enzyme for the resolution of this type of substrates; for example, trisubstituted 2,3-allenol (S)-97 was obtained with 99% ee, albeit in low yield (eqn (1), Scheme 32). 38 Bäckvall et al studied the kinetic resolution of this type of allenols using vinyl butyrate as the acyl donor and found that 4-aryl substituted allenols were resolved more efficiently than 4-alkyl substituted ones, affording the corresponding allenyl esters (R)-100 with excellent enantioselectivity.…”
Section: From Racemic Allenesmentioning
confidence: 99%
“…of 58%.29 An interesting demonstration of the versatility of esterases is provided by the resolution of the racemic organometallic ester (25) by pig-liver esterase. Both products (26) and recovered substrate (25) analogues. The exo-acetate (29) was hydrolysed very slowly and non-enantio~electively.~~ The esterase of Corynebacterium equi shows high enantioselectivity in the hydrolysis of racemic sulphoxides (30).…”
Section: Lipases and Esterasesmentioning
confidence: 95%
“…Those were employed in the kinetic resolution of racemic axially chiral molecules in both reaction directions (hydrolysis of esters and transesterification reaction). For instance, pig liver esterase was found to hydrolyze racemic allenic esters with some enantioselectivity (E value up to 42), leading to formation of the corresponding acids in 83% ee, 306,307 while lipases were used for the acylation of primary allenic alcohols by vinyl butyrate and vinyl acetate. Excellent enantioselectivities were obtained with a few substrates under perfect kinetic resolution (E value >200).…”
Section: Atroposelective Reactionsmentioning
confidence: 99%